Health indicators among low income women who report a history of sex work: the population based Northern California Young Women's Survey. Issue 5 (30th September 2005) - Cohan, D L; Kim, A; Ruiz, J; Morrow, S; Reardon, J; Lynch, M; Klausner, J D; Molitor, F; Allen, B; Green Ajufo, B; Ferrero, D; Bell Sanford, G; et al.
Abstract : Objectives: We examined differences in demographic characteristics, HIV related risk behaviour, prevalence of sexually transmitted infections (STI), and HIV and other health concerns among women with and without a history of sex work. Methods: A secondary analysis of a population based, cross sectional survey of young, low income women in northern California. Results: Of the 2543 women interviewed, 8.9% reported a history of sex work. These women reported more lifetime male sexual partners, were more likely to use drugs before sex, and were more likely to have a history of having sex with partners at high risk for HIV (that is, men who have sex with men, inject drugs, or were known to be HIV positive). They were significantly more likely to have positive serology for syphilis, herpes simplex virus type 2 (HSV-2), and hepatitis C regardless of their personal injecting drug use history; however, they were no more likely to have HIV, chlamydia, gonorrhoea, hepatitis A or hepatitis B infection compared to women without a history of sex work. Women with a history of sex work were significantly more likely to have a history of sexual coercion and tobacco use. Conclusions: These data measure the population prevalence of sex work among low income women and associated STI. Women with a history of sex work have health concerns beyond STI and HIV treatment and prevention.